Petroleum geology of Libya - Hallett, Don (Elsevier, 2002)
Libya has the largest petroleum reserves of any country in Africa and since production began in 1961 over 20 billion barrels of oil have been produced. Libya is scheduled to reach the mid-point of depletion of reserves in 2001 and this provides a timely point at which to review the state of petroleum exploration in Libya. A large amount of data has been published on the geology of Libya, but it is scattered through the literature; much of the older data has been superceded, and several of the key publications, especially those published in Libya, are difficult to find. This book represents the first attempt to produce a comprehensive synthesis of the petroleum geology of Libya. It is based exclusively on published data, supplemented by the author's experience gained during ten years work in Libya. The aim of the book is to systematically review the plate tectonics, structural evolution, stratigraphy, geochemistry, and petroleum systems of Libya, and provides valuable new data on fields, production, and reserves. This volume will provide a ready source of reference to individuals and companies who wish to obtain an overview of the petroleum geology of Libya, and will save them the laborious task of sifting through hundreds of publications to find the data they require. The book includes 148 newly drawn figures.